Construction and demolition waste managementstages - Silva, Otavio Henrique; Umada, Murilo Keith; Polastri, Paula; Angelis Neto, Generoso De; Angelis, Bruno Luiz Domingos De; Miotto, José Luiz (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The construction industry is surelyone of the most important socio-economic activities in Brazil, accounting for a share of 6.5% of gross domestic product (GDP)in 2014. However, due tolandscape change capacity, excessive consumption of natural resources and generation of waste, construction appears as a potentially degrading activity to the environment. The constructionand demolition (C&D)waste management becomes indispensable to ensure the proper disposal of this waste, in order to use the resources employed in buildings with adopting more sustainable practices. In this light, the work seeks to present the steps that must be consideredinthe management of construction and demolition (C&D) waste of different classes defined by Resolution 307/2002 of CONAMA. For this, it takes into account the previous waste characterization and later stages of segregation, packaging, transportation to treatment anddisposal of the waste concerned.